Master Narratives of Islamist Extremism - Halverson, J. author. aut Link
X, 243 p.
Keywords: This volume introduces the concept of Islamist extremist 'master narratives' and offers a method for identifying and analyzing them. Drawing on rhetorical and narrative theories, the chapters examine thirteen master narratives and explain how extremists use them to solidify their base, recruit new members, and motivate actions.